2020
DOI: 10.20944/preprints202012.0754.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Impact of Service User Video Presentations on Explicit and Implicit Stigma toward Mental Illness among Medical Students in Nepal: A Randomized Controlled Trial

Abstract: This study evaluated the impact of didactic videos and service user testimonial videos on mental illness stigma among medical students. Two randomized controlled trials were conducted in Nepal. Study 1 examined stigma reduction for depression. Study 2 examined depression and psychosis. Participants were Nepali medical students (Study 1:n=94, Study 2:¬n=213) randomized to three conditions: a didactic video based on the mental health Gap Action Programme (mhGAP), a service user video about living with mental ill… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 37 publications
1
10
0
Order By: Relevance
“…Upon examination of the students' views on the psychiatric nursing course in this study, it was found that consistent with the relevant literature, the use of techniques such as watching films, showing short videos, role‐playing, and having case studies was deemed useful for instruction by students during theoretical lectures, and a large majority of the students alleged that their basic skills in psychiatric nursing developed 16,17,30 . Moreover, the rate of students who want to work as psychiatric nurses after graduation was 6.25% before the psychiatric nursing course, whereas this rate rises to 31.25% after the course supports those students' negative beliefs toward mental illness decreased and positive psychiatric nursing perceptions increased.…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…Upon examination of the students' views on the psychiatric nursing course in this study, it was found that consistent with the relevant literature, the use of techniques such as watching films, showing short videos, role‐playing, and having case studies was deemed useful for instruction by students during theoretical lectures, and a large majority of the students alleged that their basic skills in psychiatric nursing developed 16,17,30 . Moreover, the rate of students who want to work as psychiatric nurses after graduation was 6.25% before the psychiatric nursing course, whereas this rate rises to 31.25% after the course supports those students' negative beliefs toward mental illness decreased and positive psychiatric nursing perceptions increased.…”
Section: Discussionsupporting
confidence: 64%
“…In studies analyzing the attitudes of healthcare professionals including nurses and student nurses toward mental disorders, it was found that there was no change in negative attitudes 15,17 . This is why, in the fight against stigmatization, it is emphasized to be necessary to review medicine and nursing education, and to add special education methods to change knowledge, belief, attitude, and behavior in psychiatry education programs 16,18,22,30 . It is discerned that only a very small number of studies have addressed the effectiveness of interventions toward negative beliefs, 21,25 even though there are certain studies examining nursing students' beliefs toward mental health problems in Turkey 23,24 .…”
Section: Discussionmentioning
confidence: 99%
“…Another commonly occurring theme was the use of a recovery story and seeking treatment (Finkelstein et al ., 2008; Vaghee et al ., 2015; Fernandez et al ., 2016; Ng et al ., 2017; Arthur et al ., 2020 a , 2020 b ; Potts and Henderson, 2021; Tergesen et al ., 2021). Recovery was highlighted by people with lived experience, people in contact with them (caregivers or co-workers) or through a problem-solving exercise based on a vignette story.…”
Section: Resultsmentioning
confidence: 99%
“…Social contact appears to be the most effective type of intervention to improve knowledge about and attitudes towards mental illness in the short term, though the evidence for depression specifically and for longer-term benefits is weak. 362,368,369 Investigation of workplace stigmareduction initiatives is limited, and few of these specifically target depression. 345…”
Section: Social Contactmentioning
confidence: 99%